Islamic Education Marketing Management in Review of the Al-Qur'an; Analysis of Islamic Ethics in Educational Marketing - Diana Suci Wulandari; Afina; Syafaatul Habib; Yuliharti (Akademika: Jurnal Keagamaan dan Pendidikan, 2024)
Education marketing management is very important for the sustainability of any educational institution, especially for Islamic educational institutions. The interests and desires of consumers (society) must be prioritized in marketing management in education so that excellent service can be successful and efficient. This research aims to determine the Islamic ethical values included in educational marketing management in terms of Al-Quran verses so that it is hoped that it can increase the effectiveness of academic marketing. This type of research is qualitative, using a literature review. The data collection technique in this research was carried out by taking and reviewing literature related to the topic in the form of commentaries, books, and journal articles and combining them to reach a finding. Then the data analysis technique used to compile this research is content analysis. As a result, this research found that the Islamic ethical values used to increase the effectiveness of educational marketing are: (1) justice (just), (2) honesty (Siddiq), (3) responsibility (Amanah), (4) humility (tawadhu), and (5) patience (sabr). This research concludes that when carrying out marketing activities, you must apply ethics by Islamic ethics: justice by Surah Al-Maidah verse 9, honesty by Surah At-Taubah verse 119, responsibility by Surah Al-Anfal verse 27, humility by Surah Al-Hujurat verse 11, and patience by Surah Al-Baqarah verse 153